PENYULUHAN KESEHATAN MASYARAKAT MELALUI PEMERIKSAAN LABORATORIUM SEDERHANA SEBAGAI UPAYA PEMANTAUAN KESEHATAN MANDIRI - Sugiarti, Mimi; Hartanty, Hartanty; Dinutanayo, Wimba Widagdho; Purnomo, Agus; Nurminha, Nurminha; Chaniago, Yusrizal; Amien, A. Zakaria; Djayasinga, Rodhiansyah (Poltekkes Kemenkes Bandung, 2024)
The number of cases of non-communicable diseases in Indonesia continues to increase every year. This incident can be caused by the lack of awareness of individuals in the community to carry out routine health checks so that early detection of non-communicable diseases (NCDs) based on health services becomes less effective. Prevention of NCDs risk factors and community-based prevention is one solution that can be done to reduce the risk of mortality rate due to NCDs. The purpose of this activity is to conduct health checks in the form of screening blood glucose, uric acid, and hemoglobin levels for the community in the LKSA environment of Sholawatul Fallah Orphanage, Bandar Lampung. The implementation time is Friday, August 26, 2022, at LKSA Sholawatul Fallah Orphanage, Bandar Lampung. This activity was attended by 43 residents who checked blood glucose, uric acid, and hemoglobin levels. The results obtained that as many as 43% had high blood glucose levels, 28% had high uric acid levels, and 10% with hemoglobin results below normal. The results of the examination are recommended for further examination to the Puskesmas for the Community with high blood glucose and uric acid levels.